Strategy to execution framework : a guide to strategic business analysis for enabling business transformation. (Canada : International Institute of Business Analysis, 2018)
The strategies and elements in the Strategy to Execution Framework are presented in a logical and natural order, but in practice, they may be applied in different sequential order and in parallel depending on the context and needs of individual organizations.
Preface -- Introduction -- Strategy to Execution Framework -- Implementation -- Appendix A. Key Terms -- Appendix B. Fundamental Competencies -- Appendix C: Bibliography.
Includes bibliographical references.
Keywords: STRATEGIC PLANNING